Thinking through fashion a guide to key theorists - Rocamora, Agnés; Smelik, Anneke 1956- (I.B. Tauris, 2016)
"Learning how to think through fashion is both exciting and challenging, being dependent on one's ability to critically engage with an array of theories and concepts. This is the first book designed to accompany readers through the process of thinking through fashion. It aims to help them grasp both the relevance of social and cultural theory to fashion, dress, and material culture and, conversely, the relevance of those fields to social and cultural theory. It does so by offering a guide through the work of selected major thinkers, introducing their concepts and ideas. Each chapter is written by an expert contributor and is devoted to a key thinker, capturing the significance of their thought to the understanding of the field of fashion, while also assessing the importance of this field for a critical engagement with these thinkers' ideas. This is a guide and reference for students and scholars in the fields of fashion, dress and material culture, the creative industries, sociology, cultural history, design and cultural studies."--Publisher website
Includes bibliographical references and index
Online-Ausgabe erschienen bei Bloomsbury Collections: 2020
Keywords: Fashion & society; Fashion -- Philosophy; Fashion -- Social aspects; Fashion; Mode; Ästhetik; Kunstsoziologie; Electronic books; Aufsatzsammlung